2004
DOI: 10.1051/0004-6361:20034300
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of X-ray flaring on the magnetic Bp-star $\mathsf{\sigma}$ Ori E

Abstract: Abstract. We report the detection of an X-ray flare on the Bp star σ Ori E with the ROSAT high resolution imager (HRI). The flare is shown to have likely occurred on the early-type star, rather than on an hypothesized late-type companion. We derive flare parameters such as total energy release, coarse estimates of size and density, and also present arguments for a magnetic origin of the flare. We place our observations in the context of a magnetic character of Bp-type stars and speculate on a common physical b… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
36
2

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 30 publications
7
36
2
Order By: Relevance
“…We visually inspected the X-ray light curve of σ Ori E and detected a modulation with a sinusoidal-like variation in the HRC-I count rate between 20 and 50 ks −1 and an estimated period slightly longer than the duration of the observations (>97.6 ks), which is also consistent with the rotational period. In contrast to Groote & Schmitt (2004), Sanz-Forcada et al (2004), and Caballero et al (2009), who reported strong X-ray flares in the light curves of σ Ori E, we did not find any. The flares originate in its low-mass companion ).…”
Section: X-ray Light Curvescontrasting
confidence: 99%
“…We visually inspected the X-ray light curve of σ Ori E and detected a modulation with a sinusoidal-like variation in the HRC-I count rate between 20 and 50 ks −1 and an estimated period slightly longer than the duration of the observations (>97.6 ks), which is also consistent with the rotational period. In contrast to Groote & Schmitt (2004), Sanz-Forcada et al (2004), and Caballero et al (2009), who reported strong X-ray flares in the light curves of σ Ori E, we did not find any. The flares originate in its low-mass companion ).…”
Section: X-ray Light Curvescontrasting
confidence: 99%
“…Skinner et al (2008), using data obtained with the High Energy Transmission Grating Spectrometer onboard Chandra, considered possible alternatives to the radiative wind shock, including magneticallyconfined and colliding wind shocks. Sanz-Forcada et al (2004) reported a strong X-ray flare on the magnetic B2Vp star σ Ori E, the second brightest star in the cluster, confirming the previous discovery of a flare on the star by Groote & Schmitt (2004) with ROSAT data. Caballero et al (in prep.…”
Section: Introductionsupporting
confidence: 76%
“…θ 1 Ori C shows relatively hard X-ray emission from very hot plasma at temperatures of up to 30 MK, but no strong flaring. Noteworthy, there have also been reports of X-ray flares on early type magnetic stars, a prominent example is the B2p star σ Ori E. While Groote & Schmitt (2004) attribute a flare seen with ROSAT to σ Ori E itself, Sanz-Forcada et al (2004) report a long duration (>10 h) flare with a count-rate increase by a factor of ten in an XMM-Newton observation and concluded that this more likely originates in a companion. They derived a QQ X-ray luminosity of L X = 9 × 10 30 erg s −1 and plasma temperatures up to 10-15 MK for σ Ori E. Also non CP, magnetic early-B stars are X-ray sources, e.g.…”
Section: What About Hotter Magnetic Stars?mentioning
confidence: 99%